Criteria for difficult biliary cannulation: start to count. Issue 10 (October 2019) - Ismail, Shamel; Udd, Marianne; Lindström, Outi; Rainio, Mia; Halttunen, Jorma; Kylänpää, Leena
Abstract : Objective: In European Society of Gastrointestinal Endoscopy guidelines, biliary cannulation of native papilla is defined as difficult in the presence of >5 papilla contacts, >5 min cannulation time or >1 unintended pancreatic duct cannulation (5-5-2). The aim is to test 5-5-2-criteria in a single-center practice predicting the risk of post-endoscopic retrograde cholangiopancreatography pancreatitis (PEP), and to study the efficacy of transpancreatic biliary sphincterotomy (TPBS) as an advanced method for biliary cannulation. Methods: Prospectively collected data of 821 patients with native papilla were analyzed. Primary cannulation was the first method chosen for cannulation (sphincterotome and a guidewire). Advanced cannulation method was endoscopist-chosen cannulation method after failed primary cannulation. Results: Primary cannulation succeeded in 599 (73%) patients in a median of 2 min. TPBS ± needle knife resulted in a 90% success rate. The final cannulation success was 814 (99.1%) cases in a median of 5.3 min. PEP risk was 4.0%. When primary cannulation succeeded, the PEP rate was 2.3%. When advanced methods were needed, the PEP rate increased to 13.5%. Altogether 311 (37.9%) patients fulfilled at least one 5-5-2-criterion. In patients without 5-5-2-criteria, the primary cannulation succeeded in 79.6% (n = 477), compared to 20.4% (n = 122) with the criteria, P < 0.001, indicating the need to exchange the cannulation method instead of persistence. If all the 5-5-2-criteria were present, the risk of PEP was 12.7%. Conclusion: The results support the use of the 5-5-2-criteria for difficult cannulation. TPBS is an effective advanced cannulation method with an acceptable complication rate.